Pemanfaatan Media Sosial Instagram Akun @Mahasiswaakhir.Id Sebagai Media Literasi Informasi Mahasiswa - Septia Ningsih; Fitria Yuliani; Eceh Trisna Ayuh (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
This study aims to see how the use of social media Instagram account @mahasiswaakhir.id as a medium for information literacy in students. This study uses qualitative methods with participatory observation data collection techniques and interviews. The research results show that the @mahasiswaakhir.id account is an Instagram account that seeks to become an information literacy medium, especially for students by providing relevant information in the form of video tips and tutorials as well as motivational content that can help and benefit students. This shows that the @mahasiswaakhir.id account utilizes Instagram social media as an information literacy medium for students by providing video content information, tutorial tips and motivation to students so that students can choose and process information according to their needs. The conclusion of this study is that social media has been utilized as well as possible to disseminate information. Keywords: Account @mahasiswaakhir.id, Information literacy, Instagram, Students,